(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Co-infection of parasitic disease and pulmonary tuberculosis are increasing public health problem especially in developing countries like Bangladesh. More than 81% of cases and deaths from TB are in developing countries and is aggravated by concurrency with parasitic diseases, where in Bangladesh suffer a substantial no of Kala-azar cases in each year. Cattle are found to have bovine tuberculosis but at the same areas of Kala-azar endemicity, whether this animal found to be positive. Objectives: To findout the concurrent infection in humans and animals in Kala-azar endemic areas of Bangladesh. Materials and Methods: This study was conducted at Surya Kanto Hospital, Mymensingh and four Kala-azar endemic Upazilla of Mymensingh, Tangail and Pabna District. A total of 300 highly suspected tuberculosis patients reported from Kala-azar endemic areas and 170 cattle’s blood sample, 110 cattle spleen samples were included in this study. Cattle blood and spleen samples were investigated for both TB and Kalaazar and all the TB cases were investigated for Kala-azar. Buffy coat from venous blood was taken for ELISA and PCR. Spleen samples were sonicated and then were examined by PCR. All patients’ blood was tested with ICT (rK39) for Visceral Leishmaniasis. ICT positive patient’s splenic aspiration was examined by smear microscopy with 10x 100 magnifications. After that, all these samples were tested by ELISA and PCR. Results: Out of total 300 patients 162(54%) were found positive for TB. Blood sample of 180 patients was tested with ICT rK39 and 12(7%) patients were found positive for leishmaniasis who suffered from Tuberculosis. These 12(7%) patient’s splenic smear were examined of which 11(92%) of them were found positive for leishmania. But using ELISA all 12(100%) patient smears were found positive. Out of 170 cattle blood 12(7.1%) were ICT positive indicating prevalence of bovine tuberculosis and of these 170 cattle blood 20(11.8%) were found positive for antileishmania antibody. With PCR of these 20, no one was found positive for Leishmania. Conclusion: Visceral leishmaniasis and tuberculosis coinfection have drawn attention clinically. This study found the presence of leishmaniasis and tuberculosis concurrently in humans in Kala-azar endemic areas, wherein bTB antibody was detected in cattle. Though concurrently leishmania antibody was found in cattle but was not proved by PCR which requires further studies. Journal of Armed Forces Medical College Bangladesh Vol.14 (2) 2018: 91-96